PEMBUATAN SISTEM DETEKSI TELUR PADA INKUBATOR DENGAN CMU CAM BERBASIS IoT - LEGAWA, MOHAMAD ASHARI NURSAGARA; HARTAWAN, LIMAN (e-Proceeding FTI, 2024)
As the chicken farm develops, it must also be balanced with the development of the farm to incubate the chicken eggs. In this routine, various aspects must be considered, such as the appropriate incubator, temperature, humidity and also at the time of hatching the chicken eggs because when the eggs have hatched they are not immediately removed from the machine. hatchers, the chicks can die because they are in the egg incubator for too long, they also become dehydrated, and can interfere with the hatching process of other eggs. The temperature of the hatching room during the incubation period of the chicken eggs (first 18 days) is set at around 37°-38.5°C, while during the hatching period (around day 19-21) the temperature can be raised slightly to 39°C or kept at 38°C. . Relative humidity, during the incubation period, humidity is maintained at 50% - 55%. From the aspects described above, an Egg Incubator Incubator was made with an IoT- based CMU CAM so that the temperature can be controlled with a lamp that warms up the incubator with an ideal distance of 8 cm and will turn off when the temperature touches >38°C. When the hatching process occurs CMU CAM with Image Tracking Sensors will notify so that the eggs change shape as they hatch will be detected by the Pixy 2 CMU CAM. Abstrak Semakin berkembangnya peternakan ayam maka harus diimbangi juga dengan perkembangan peternakan untuk menetaskan telur ayam tersebut. Dalam Rutinitas tersebut harus diperhatikan berbagai aspek seperti inkubator yang sesuai, temperatur, kelembaban dan juga pada saat penetasan telur ayam dikarenakan saat telur yang telah menetas tidak segera dikeluarkan dari mesin penetas maka anak ayam bisa mati karena terlalu lama berada di dalam mesin penetas telur juga mengalami dehidrasi, dan dapat mengganggu proses penetasan telur lainnya. Temperatur ruang tetas pada masa pengeraman telur ayam (18 hari pertama) diatur sekitar 37°-38,5°C, Sedangkan pada masa penetasan (sekitar hari ke 19-21) suhu bisa dinaikkan sedikit hingga 39°C atau tetap dibiarkan 38°C. Kelembabannya relatif, pada periode pengeraman, kelembaban dijaga pada 50% – 55 %. Dari aspek yang dijelaskan tersebut maka dibuatlah Inkubator Penetas telur dengan CMU CAM berbasis IoT sehingga Temperatur bisa dikontrol dengan lampu yang menghangatkan inkubator dengan jarak ideal 8 cm dan akan mati ketika temperatur menyentuh >38°C .Saat proses penetasan terjadi CMU CAM dengan Image Tracking Sensor akan memberi tahu sehingga telur berubah bentuk karena menetas akan terdeteksi oleh Pixy 2 CMU CAM.